HUBUNGAN PRAKTEK PENANGANAN SAMPAH DI KAWASAN KUMUH TERHADAP KEJADIAN PENYAKIT DIARE (STUDI KASUS DI KECAMATAN LIMA PULUH KOTA PEKANBARU) - Nurhapida Nurhapida; Sofyan Husein Siregar; Zahtamal Zahtamal (Program Pascasarjana Universitas Riau, 2019)
Diarrhea is one of the main causes of illness and even death associated with waste management. This study aims to analyze the relationship of waste management with the incidence of diarrhea in the slums of District Lima Puluh of Pekanbaru City. Survey method was conducted through observation and distribution of questionnaires on 326 respondents related to education, length of stay, income, knowledge and practice of garbage collection. The data obtained was analized by logistic regression. The results of the study found that 33 outbreaks of diarrhea from 326 bigger respondents occurred in the low level of garbage collection of respondents. Characteristics of length of stay, knowledge and practice of garbage collection have a mutual influence on the occurrence of diarrhea with an influence contribution of 33.9%. Partially, only garbage collection practices have a significant effect on the occurrence of diarrhea (p <0.05; OR = 66.695) which means that respondents with poor waste collection practices have a 66.695 times chance of getting diarrhea compared to respondents with garbage collection practices good. Municipal Government of Pekanbaru City is very important to pay attention to this aspect and improve the service of garbage transportation to realize better settlement society to be able to avoid the occurrence of diarrhea incidence.